Observing the behavioural effects of methylphenidate in children and adolescents with ASD-ADHD dual diagnosis: A mini review - Dimitri, Danilo; Delia, Giuliana; Arduino, Maurizio; Turco, Nazarena; Fioretto, Franco (Frontiers in Child and Adolescent Psychiatry, 2023)
Research aim The aim of this study is to focus on the main neurophysiological aspects of attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) and the current pharmacological treatment used for the management of hyperactivity and attention deficits in children aged 6-20 years with a diagnosis of ASD, not associated with other genetic or epileptic disorders, such as Fragile X Syndrome (FXS), Tuberous Sclerosis, Kleefstra Syndrome or Angelman Syndrome. Methods This mini review was conducted according to the P.I.C.O. model and according to the PRISMA guidelines. The keywords used were: autism spectrum disorder; attention deficit hyperactivity disorder; attention deficit disorder; methylphenidate; ritalin; ADHD; youth autism; childhood autism; childhood autism spectrum disorder; adolescent autism. The strings produced were compared and selected by a third independent clinician. The PubMed and PsycArticles search yielded a total of 3,200 articles. For their inclusion, the 3,200 articles were examined by two clinicians who ultimately selected 28 (15 clinical trials and 13 reviews/meta-analyses) articles analysed according to their consistency with the inclusion and exclusion criteria. Conclusions Three main aspects emerged from the review: (1) According to the existing literature, new randomized controlled trials are needed to ensure a better understanding of the most effective drug treatments for dual-diagnosed ASD-ADHD patients and of the related behavioural effects. Currently, the use of drugs varies depending on psychiatric comorbidity, symptoms, age and gender and there is no univocal reference therapy; (2) Methylphenidate (MPH) has currently been shown to be the most suitable drug for the treatment of hyperactivity and inattention in individuals diagnosed with ASD and ADHD; (3) There is a need to create and evaluate appropriate tests to analyse more specific patterns of behaviour presented in the two conditions.